Peran Orang Tua dalam Pembentukan Identitas dan Perilaku Anak (Parental Influence on Children’s Identity Formation and Behavior) - Wahyuni S Dunggio, Sri (Happiness: Journal of Psychology and Islamic Science, 2026)
This study aims to analyze the influence of parental roles on the formation of children’s identity and behavior, as well as the impact of limited parental involvement on children’s psychological development. Using a library research approach, this study reviews approximately 30 scientific sources obtained from Google Scholar and national and international journal databases, including journals, books, and scientific articles related to developmental psychology and parenting practices, with data validity strengthened through source triangulation. Findings indicate that children who lack guidance, attention, and emotional attachment from parents are at risk of identity confusion, impulsive behavior, low self-confidence, and social adjustment difficulties. Active, warm, consistent, and responsive parental involvement supports stable identity formation and adaptive behavior, highlighting the critical role of parents in optimal child psychological development.